Capture Efficiency of Torrent Ducks by the Active Mist-Net Method - Alza, Luis (2017)
We report on the use and efficiency of an active mist-net method for capturing 3 subspecies of torrent ducks (Merganetta armata), a territorial and specialized South American waterfowl, in fast-moving rivers of the Andes Mountains. As an active process, the execution of this methodology required the presence of a well-trained, 3-person team. During the austral winter and spring between 2010 and 2014, we captured 372 torrent ducks in 410 capture events on 8 different rivers in Colombia (n = 1), Peru (n = 5), and Argentina (n = 2). Each captured torrent duck was banded and 32 opportunistic recaptures were obtained using the same methodology in the same territories. We deployed the mist-net across fast-moving deep rivers, along elevational gradients (680?4,200 m). Males were more easily captured than females, because of their greater tendency to fly. Our data validated this capture method for torrent ducks, as we succeeded in capturing individuals of the 3 subspecies in different habitats at different elevations and latitudes. To avoid animal mortality, we recommend application of this method only when 3 minimal conditions are met: 1) each field crew has at least 3 people; 2) all of the crew members have hand-radios to enable continuous communication, and 3) each crew member has received prior training (e.g., installation, inspection, manipulation and removal of the mist net, bird extraction, and familiarity with the behavior of the ducks).